Effect of mouthrinses on discolouration of CAD-CAM manufactured temporary restorative materials - Aparna.J; Dr. Karthickraj S M (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Aim: The main aim of this study was directed to evaluate the in vitro effect of mouth rinses on colour stability of Computer-aided design and computer-aided manufacturing (CAD-CAM) temporary restorative materials. Materials And Methods: In this study CAD-CAM manufactured polymethylmethacrylate (PMMA) blocks were used. A total of 8 samples of PMMA blocks with shade A2 (10 mm in diameter and 2 mm in thickness) were constructed in standardized manner and were collected from the CAD-CAM department of Saveetha dental college. The blocks were mounted and preoperative values for color stability were recorded using spectrophotometry. Samples were divided into four main equal groups. In total, 4 different mouthrinses for each group. Color changes were measured with a digital spectrophotometer after 7 days and specimens were prepared. The data was collected, tabulated and subjected to statistical analysis using SPSS Statistics Version 23. Results And Discussion: Significant discolouration was observed in all groups after the immersion in mouthrinses. It shows that Herbal mouthrinse and distilled water(control) have good colour stability whereas listerine mouthrinse has the least colour stability. Conclusion : The CAD-CAM blocks were susceptible to color changes following immersion in the tested mouthrinses. Discoloration effect of the tested mouthrinses on various CAD-CAM materials was comparatively different.